Supervisi Akademik Sebagai Upaya Peningkatan Kompetensi Guru dalam Penyusunan Silabus dan RPP di Madrasah Tsanawiyah Kecamatan Surade Kabupaten Sukabumi - Arifin, Widad (Lembaga Rumah Indonesia, 2021)
The learning planning process that a teacher must carry out includes the following main activities: (1) Creating an annual program, (2). Making a syllabus, (3). Creating a semester program, (4). Make a learning implementation plan, (5). Furthermore, make a test/evaluation program. Of the five elements above, the syllabus and lesson plans are the minimum preparation for a teacher when teaching. Based on the analysis results in the 2018/2019 academic year at MTs Surade District, the problem arises that the lack of teachers who make lesson plans, especially the preparation of syllabus and lesson plans. To examine teachers' weak performance in this regard, a study was conducted to see how steps of academic supervision of madrasah principals can improve teacher competence in the preparation of syllabus and lesson plans. This research was conducted with a classroom action research method that lasted for two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The results of this study indicate that ongoing academic supervision has been scientifically proven to improve teacher competence in compiling syllabus and lesson plans at MTs Surade District. It is evidenced by the increase in the number of good teacher syllabus from 31% to 83% after academic supervision. Besides, the number of good quality RPPs also increased from 31% to 89%.